The jury in Ukraine: topical issues of reforming - Рощина, Інна Олександрівна; Циганій, Світлана Олексіївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
Despite the age positive practices of the jury in the world, in Ukraine in 2012, the adoption of the Criminal Process Code of Ukraine, attempted introduction of jurors is completely different both in form and in substance from the Institute of Chartered worldwide. Therefore, this innovation does not give positive results both in preventing corruption in the judiciary and the legitimacy to prosecute the accused. The current state of the jury in Ukraine fully investigated. Analysis of recent research shows that the response to this innovation has been somewhat controversial. Provisions of the Criminal Code of Ukraine (art. art. 31, 368 CPC of Ukraine), which regulate the activity of the jury, completely not only meet the international practice of trial by jury, but does not contribute as prevention of corruption in the judiciary and the legality of prosecution criminal liability of persons who committed or not committed crimes. Summarizing the analysis of the status of the jury in Ukraine and the world practice the jury should be noted that the introduction of urgently needed according to international practice. In our opinion, the number of jurors in Ukraine for crimes with penalty of imprisonment of three years and above, should be 9 people. For crimes for which capital punishment less than three years in prison, the number of jurors to be six men and only at the request of the accused. A panel of jurors must sit separately from the court and communicate with him only through its elected chairman of the board.